Load simulation and substantiation of design values of a pin flexible coupling with a flexible disk-type element - Ruslan S. Melezhik; Dmitry A. Vlasenko (Горные науки и технологии, 2021)
In the process of operation of present-day mechanical equipment, dynamic loads arise, leading to the failure of parts, assemblies and mechanisms and, thus, reducing the equipment life time and operational reliability. A method has been developed for calculating the design and technological values of a pin flexible coupling with a flexible disk-type element, using the method of central compositional rotatable uniform planning of the second order and the finite-element method for calculating stresses using a computer-aided design system. The analytical dependence of the torque on the PCD (pin (centers of holes for pin) circle diameter) and the width of the flexible element with certain physical and mechanical properties was substantiated, on the basis of which the formula for the total width of the flexible disk-type element was obtained, taking into account the value of the required torque and the given PCD. In order to check the obtained dependence of the nominal torque, an additional study of couplings with the given PCD was carried out at different total width of the flexible element. The implemented research allowed determining the influence of the design characteristic values on the transmitted torque of a pin flexible coupling with a flexible disk-type element. A standard-size range of couplings with certain design and technological values has been proposed.